Factors that promote new or continuous participation in social group activity among Japanese community‐dwelling older adults: A 2‐year longitudinal study. Issue 8 (12th July 2018) - Nemoto, Yuta; Nonaka, Kumiko; Hasebe, Masami; Koike, Takashi; Minami, Ushio; Murayama, Yoh; Murayama, Hiroshi; Matsunaga, Hiroko; Fukaya, Taro; Kobayashi, Erika; Maruo, Kazushi; Fujiwara, Yoshinori
Abstract : Aim: Identifying factors that influence participation in social group activities in older adults might be helpful in promoting social participation in this population. We examined factors related to new or continuous participation in social group activities according to group type. Methods: We carried out a community‐based, longitudinal study with a 2‐year follow‐up period. Of 7608 older adults aged ≥65 years, 3380 completed the follow‐up survey and were included in the analysis. We examined private group (hobbies, sports and volunteering; PrG) and public group (neighborhood associations and senior citizen clubs; PuG) activity. Results: For PrG, 39.6% of the participants were engaged at baseline, 25.5% initiated participation and 9.5% withdrew during the study period. For PuG, 20.8% of the participants were engaged at baseline, 10.8% initiated participation and 31.5% withdrew during the study period. Logistic regression analysis showed mental health, self‐rated health, employment, relationships with neighbors, subjective economic status, educational attainment and participation in PuG were related to new participation in PrG. Mental health, employment and relationships with neighbors were significantly related to continuous participation. For PuG, mental health, sex and relationships with neighbors were significantly related to new participation, whereas sex, relationships with neighbors and educational attainment were related to continuous participation. Conclusions: The rate of new and continuous participation in PrG was higher than that in PuG, and different related factors were identified as existing between social group types.Geriatr Gerontol Int 2018; 18: 1259–1266 .